Nano-titania doped with europium and neodymium showing simultaneous photoluminescent and photocatalytic behaviour1. Issue 19 (21st May 2015) - Tobaldi, D. M.; Ferreira, R. A. S.; Pullar, R. C.; Seabra, M. P.; Carlos, L. D.; Labrincha, J. A.
<x xml:space="preserve">Abstract</x> Titanium dioxide (TiO2) nanomaterials are attracting increasing interest, mostly because of their superior photocatalytic and antibacterial properties.